1998
DOI: 10.1046/j.1365-2168.1998.00601.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the introduction of total mesorectal excision for the treatment of rectal cancer

Abstract: Anastomotic dehiscence increased after introduction of the TME technique but this improved with experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
172
2
10

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(195 citation statements)
references
References 15 publications
11
172
2
10
Order By: Relevance
“…The introduction of TME surgery can be associated initially with higher rates of anastomotic leakage, but several studies showed that these findings would improve during the routine application of TME surgery [21-23]. During the time of our study there were 4 of 78 cases with a clinical apparent anastomotic leakage.…”
Section: Discussionmentioning
confidence: 83%
“…The introduction of TME surgery can be associated initially with higher rates of anastomotic leakage, but several studies showed that these findings would improve during the routine application of TME surgery [21-23]. During the time of our study there were 4 of 78 cases with a clinical apparent anastomotic leakage.…”
Section: Discussionmentioning
confidence: 83%
“…These differences of recurrence rates may be explained by retrospective design of the majority of the studies and the heterogeneity of the patient groups. There are some publications that suggest that total mesorectal excision is the surgical technique with the lowest rate of local recurrence (Enker et al, 1995;Arbman et al, 1996;Heald et al, 1998;Carlsen et al, 1998;Havenga et al, 1999;Leo et al, 2000). Prospective studies for adjuvant therapy in the group with Stage I rectal cancer are limited (Steele et al,1999;Russell et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons before and after training workshops in Norway in the early 1990's in the TME technique documented LRR rates that decreased from 16% to 8% [8]. Likewise, a systematic training program established in Stockholm from 1994 to 1995 changed the definitive surgical procedure from non-TME resection to TME resection and LRR decreased from 15% to 6% with surgery alone [9].…”
Section: Total Mesorectal Excision Decreases Local Recurrencementioning
confidence: 99%